PEMANFAATAN FIREBASE REALTIME DATABASE PADA APLIKASI PEMBELAJARAN AGAMA ISLAM MENGGUNAKAN FRAMEWORK FLUTTER - Femi Dwi Astuti; Yogo Hermawan (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2020)
Smartphone is now a device that is in great demand by children. In addition to playing, smartphones can be used for learning for children. Making mobile applications is often considered difficult because it requires high laptop specifications, but with all the flutter resolved. Firebase is able to connect mobile applications to cloud storage. One feature of firebase is the realtime database. This is very suitable to be applied for learning applications that require changing the theory periodically. The results showed that the application of Islamic learning for children using flutter framework can help the process of learning Islam because it can be done anywhere. Theory and questions can change automatically without having to be refreshed by the user.